Classical Studies in the St Petersburg Imperial Academy of Sciences in the 19th – early 20th centuries - Basargina, Ekaterina (Hyperboreus, 2014)
The article embraces the history of Classical studies in the St Petersburg Academy of Sciences, from its foundation in 1724 up until 1917. The author sketches the activity of Sergei Uvarov and Dmitry Tolstoy’s educational reform, outlines the foundations of the Teachers College for Slavic Grant holders and Historic-philological institutes in St Petersburg and Nezhin, and describes the outstanding representatives of St Petersburg Classical scholarship of the 2nd half of the 19th and the early 20th century. In closing some data regarding the history of Russian Classical archaeology and Byzantine studies is adduced.